Low density parity check matrices for coding of multiple access networks - Muramatsu, J.; Uyematsu, T.; Wadayama, T. (2003 IEEE Information Theory Workshop : proceedings : La Sorbonne, Paris, France, 31 March-4 April, 2003, 2003)
The paper considers linear matrices for a coding problem for multiple access networks. It is proved that we can construct codes by using sparse matrices, which are also called low density parity check (LDPC) matrices.